Plasma Markers of Oxidative Stress in Patients with Gestational Diabetes Mellitus in the Second and Third Trimester - Hongwei Li; Qian Yin; Ning Li; Zhenbo Ouyang; Mei Zhong (Obstetrics and Gynecology International)
Objective. To determine plasma markers of oxidative stress during the second and third trimester of pregnancy in patients with gestational diabetes mellitus (GDM). Study Design. We conducted a prospective nested case-control study involving 400 pregnant women, 22 of whom developed GDM. As control group, 30 normal pregnant women were chosen randomly. Plasma samples were analyzed for 8-iso-prostaglandin F2α (8-iso-PGF2α), advanced oxidative protein products (AOPPs), protein carbonyl (PCO), glutathione peroxidase-3 (GPX-3), and paraoxonase-1 (PON1) at 16–20 weeks, 24–28 weeks, and 32–36 weeks of gestation. Results. Compared to control subjects, the plasma levels of PCO, AOPPs, and 8-iso-PGF2α were elevated at 16–20 weeks’ and 32–36 weeks’ gestation in GDM. There was no significant difference in PCO and 8-iso-PGF2α at 24–28 weeks in GDM. GPX-3 was statistically significantly increased at 16–20 weeks and 32–36 weeks in GDM. PON1 reduced in patients with GDM. No significant differences were found at 24–28 and 32–36 weeks between the GDM and control groups. In GDM, PCO, AOPPs, and 8-iso-PGF2α levels were higher and GPX-3 and PON1 levels were lower in the second than the third trimester. Conclusion. Oxidation status increased in GDM, especially protein oxidation, which may contribute to the pathogenesis of GDM.